Machiavellianism and Corporate Ethical Values as Determinants of Accountants’ Ethical Decision Making - Pulungan, Andrey Hasiholan; Fitriningrum, Andriati (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2019)
This study aims to evaluate the extent to which ethical environment may moderate the negative effect of Machiavellianism towards accountants? ethical decision making. Questionnaires are distributed to accountants work in various company in Jakarta. The study finds accountants with High Machs are more likely to take unethical actions, while corporate ethical values (CEV) may encourage accountant to act more ethically. However, CEV does not reduce the negative effect of Machiavellianism towards accountants? ethical decision making. This study contributes to accounting literature by providing evidence on how weak ethical environment may trigger accountants to act unethically.